Pengaruh Manajemen Ekstrakurikuler terhadap Hafalan Hadits Arba’in Siswa Kelas VI di MIS Darul ‘Ilmi Desa Karang Jaya Teras Terunjam - Aprizal Aprizal (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The results of observation, memorization of Hadith Arba'in at MIS Darul 'Ilmi that out of 16 students in the 2022/2023 school year, only 63% or around 10 students and 78% in 2023/2024 managed to reach the target of memorizing 15 Hadith, this shows a significant difference between what is expected and what actually happens. The purpose of the research is to study and evaluate extracurricular management at MIS Darul 'Ilmi thoroughly and in depth. This research is quantitative with a correlational descriptive design. The research was conducted at MIS Darul 'Ilmi, Karang Jaya, Teras Terunjam. The population was all grade VI students with saturated sampling technique. Data collection using questionnaires, tests, observations, and interviews. Data analysis techniques are descriptive and inferential analysis. The results of the research obtained on the presence or absence of the influence of extracurricular management on memorizing Hadith Arba'in there is a positive and significant relationship and influence, which is 37.21%. This means that in extracurricular activities management is needed and plays an important role in the implementation process in terms of planning to evaluation.